Measurement of catechin and gallic acid in tea wine with HPLC - Li, Yongjun (Saudi J Biol Sci, 2020)
First a kind of fermented tea wine was prepared from Dancong tea. The content of four major catechins and gallic acid (EC, EGC, EGCG and ECG) in tea wine was measured with HPLC. The results showed that the content of EC, EGC, EGCG, ECG and catechins in tea wine decreased when compared with that before fermentation. The content of EC decreased the most, reaching 26.79%, while the content of GA changed the least with a decrease of only 13.56%. Nevertheless, tea wine still contains a relatively large amount of catechins, thus proper consumption of tea wine may be salubrious.